Revitalisasi Air Bersih melalui Impelmentasi Sistem Pipanisasi di Desa Bango Kepulauan Mantehage, Sulawesi Utara - Emma Mauren Moko; Dino Rahardiyan; Ferry Wantouw (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. Bango Village is one of four the villages of Mantehage Island along with the villages of Buhias, Tinongko and Tangkasi. These villages of Mantehage Island are clustered in the district of Wori, within North Minahasa Regency. Mantehage along with 4 other islands (Nain, Manado Tua, Siladen and Bunaken) are the isles of the Bunaken Marine Conservation (Taman Laut Nasional Bunaken), all collected in a cluster of islands spanning out at about 89.065 hectars. Cleanwater has been a priority agenda for the dwellers of these islands, as is so for 120 households in Bango Village. Cleanwater for sanitary activities and other household activities are all sourced from the one and only village well that is about 500m away from the docks, which villagers must walk the distance to fetch water for their needs. Not to mention the fact that the water conditions are brackish with high salinity. The previous phase of this program had installed a 5500ltr water tank on a modular recycled light steel gauge tower that was also equipped with a 3-stage filter. The previous continuation of the program this year concluded with a plumbing network connecting to 60 households from the well to the docks. The impact of this current achievement in this cleanwater revitalization program was the change in sanitary habits of the people which now is not centralized at their village well, but can be done at their homes, while for some would share with others for the meantime.